Reviewing the effect of teachers’ resilience and wellbeing on their foreign language teaching enjoyment - Zhang, Linlin (Frontiers in Psychology, 2023)
This paper reviews evidence on teachers’ resilience (TR) and wellbeing (TWB) on foreign language teaching enjoyment (FLTE). This review improves the understanding of the multi-dimensional, dynamic and context-dependent structural attributes of TR and TWB, as well as the relationship between them and the FLTE. The literature review verifies the positive effects of teachers’ positive optimism, self-efficacy, positive teacher-student relationship, teacher support and pro-social dynamic classroom environment on TR and TWB under person-context interaction, and also confirms that TR and TWB have predictive effect and significant impact on personal enjoyment, social enjoyment and student appreciation of FLTE three-factor structure. Some important findings from the review verifies the important role of teachers’ social enjoyment in the three-factor structure and the dominant role of prosocial situational characteristics in predicting FLTE. This paper finally explains its pedagogical significance and provides some suggestions for expanding the research on antecedent variables related to FLTE.